APPROACHES TO EVALUATION OF THE COMPANY INNOVATION ACTIVITY - Oleg E. Kalenov (Вестник Российского экономического университета имени Г. В. Плеханова)
Innovation component of the company development is a key source of its growth. Due to increasing internal and external competition innovation becomes the most important component of management oriented to strategic success. The author identifies four basic directions of the company innovation activity: developing new products, modernizing existing goods, developing new technological process, upgrading industrial equipment. For each of these directions the author designs a system of indicators which can allow the manager to evaluate the efficiency of work. The approach to evaluation of the total innovation activity of business was described. For this purpose the author shows direct and indirect indicators of the company innovation activity.